In vitro and in vivo studies of biodegradable Zn-Li-Mn alloy staples designed for gastrointestinal anastomosis. (February 2021) - Guo, Hui; Hu, Jili; Shen, Zhenquan; Du, Dexiao; Zheng, Yufeng; Peng, Jirun
Abstract: Zn-0.8 wt.% Li-0.1 wt.% Mn wire with the diameter of 0.3 mm was fabricated and further processed into gastrointestinal staple, and its in vitro and in vivo biodegradation behavior and biocompatibility were studied systematically. The experimental Zn-Li-Mn alloy staple could deform from the original U-shape to B-shape without fracture, indicating its good mechanical property. Due to the residual stress concentration caused by anastomosis deformation, the feet and leg arc part of the staple were more prone to degradation. The Zn-Li-Mn alloy staple sustained integrity after immersion in Hanks' solution and simulated gastric fluid (SGF) for 28 days, and the degradation rate in SGF was about 4 times of that in Hanks' solution. Furthermore, Zn-Li-Mn alloy staples were utilized for gastrointestinal anastomosis in pig models, with clinically-used titanium alloy staples as a comparison. No anastomotic leakage and severe inflammation were observed after operation. The Zn-Li-Mn alloy staple maintained mechanical integrity within 8 weeks' implantation. The gastrointestinal tissue healed after 12 weeks, and no obvious side effects were detected during the whole implantation period, demonstrating the good biocompatibility of Zn-Li-Mn alloy staple. Thus, Zn-Li-Mn alloy staple fabricated in this work displayed the promising potential in the gastrointestinal anastomosis. Graphical abstract: Image, graphical abstract